Combination of ROC and MFEP Methods in Providing Credit to the Mislina Cooperative - Fauzya, Firda; Maharani, Dewi; Sumantri, Sumantri (Sistemasi: Jurnal Sistem Informasi, 2024)
One of the activities of the cooperative is to offer loans to customers and make loans based on several requirements that must be met by applicants who wish to borrow. So far, in determining the provision of cooperative loans to mislina cooperatives, it is considered that they are not careful and selective in providing loans which has an impact on increasing the ratio of loans in arrears. The process of granting loans to mislina cooperatives is still done manually and without doing calculations with special calculation methods that can help do rankings. The research objective was to apply the ROC and MFEP combination methods in designing a decision support system for mislina cooperative loan assessments. The method used is a decision support system using a combination of ROC and MFEP methods. Based on the results of implementing a combination of ROC and MFEP, the results of the system being built can make it easier to determine the provision of pimjama loans to Mislina cooperatives so that they are more effective and efficient. The results of the ROC and MFEP combination tests resulted in a decision that the highest alternative was sayem with a final total value of 2.85.